Obraz grzeczności na przykładzie reakcji na komplementy polskich i niemieckich studentów . - Frankowska, Violetta (Investigationes Linguisticae, 2011)
The growing interest in politeness phenomena clearly points to the importance of the issue in our life. Living with other people, one should consider other peoples’ feelings and needs in order to be polite. Politeness is inevitably reflected in language and differs cross-culturally. It is common that certain forms of behavior are acceptable and appropriate in one culture, but not successful in the other one. The aim of this article is to present the concept of politeness on the basis of how Polish and German students respond to compliments. Such knowledge promotes harmonious intercultural relations.